Peripheral refraction in myopic eyes after LASIK surgery - Queirós, A. (2012)
PURPOSE: To characterize the axial and off-axis refraction across the horizontal meridian of the visual field before and after myopic laser-assisted in situ keratomileusis (LASIK) surgery. This research took place at the Clinical Ophthalmologic-NovoVisión, Madrid, Spain. METHODS: Twenty-six ODs (mean age ± SD = 30.4 ± 4.8 years) of 26 patients who underwent LASIK surgery to treat myopia between -0.75/-3.88 D of spherical equivalent (M) were included in the study. Peripheral refraction was evaluated by an open field auto-refractor before and after LASIK surgery at 3 months. Along with a complete set of examination procedures to assess suitability for treatment, the central and peripheral refractions were measured along the horizontal meridian up to 35° of eccentricity in the nasal and temporal retinal areas in 5° visual field steps. RESULTS: Changes in M ranged between 1.85 ± 0.93 D at center to 0.33 ± 0.73 D at 35° in the nasal retina (p < 0.029 for all eccentricities). Treatment induced was symmetric between nasal and temporal visual fields along the horizontal meridian. The degree of myopic increase in relative peripheral refractive error as represented by the spherical equivalent for 30° (r2 = 0.462, p < 0.001) and 35° (r2 = 0.717, p < 0.001) eccentric refraction was correlated with axial spherical equivalent at baseline. CONCLUSIONS: Peripheral refraction is affected by myopic LASIK surgery. Unlike orthokeratology, which increases the peripheral myopia, LASIK reduces myopia across the horizontal visual field out to at least 35° from fixation.